2019
DOI: 10.1111/1755-0998.13106
|View full text |Cite
|
Sign up to set email alerts
|

EnTAP: Bringing faster and smarter functional annotation to non‐model eukaryotic transcriptomes

Abstract: EnTAP (Eukaryotic Non‐Model Transcriptome Annotation Pipeline) was designed to improve the accuracy, speed, and flexibility of functional gene annotation for de novo assembled transcriptomes in non‐model eukaryotes. This software package addresses the fragmentation and related assembly issues that result in inflated transcript estimates and poor annotation rates of protein‐coding transcripts. Following filters applied through assessment of true expression and frame selection, open‐source tools are leveraged to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
133
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 167 publications
(136 citation statements)
references
References 28 publications
3
133
0
Order By: Relevance
“…On average, the Illumina isoforms (7,220 bp) were longer than the PacBio isoforms (6,044 bp). By running the EnTAP functional annotation pipeline with the entire NCBI RefSeq plant database (Hart et al 2018), we observed that 672 isoforms were annotated with a plant protein, while the remaining 486 transcript isoforms were not identified in the previous walnut gene annotation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On average, the Illumina isoforms (7,220 bp) were longer than the PacBio isoforms (6,044 bp). By running the EnTAP functional annotation pipeline with the entire NCBI RefSeq plant database (Hart et al 2018), we observed that 672 isoforms were annotated with a plant protein, while the remaining 486 transcript isoforms were not identified in the previous walnut gene annotation.…”
Section: Resultsmentioning
confidence: 99%
“…The percent identity and coverage of each J. regia transcript compared to proteins in the NCBI plant RefSeq database was also determined by running the EnTAP pipeline v.0.9.0 (Hart et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The EnTAP functional annotation package was employed to remove unlikely gene models and provide provisional functional information (Hart et al , ). Multi‐exonic and mono‐exonic gene models were subjected to different functional filtering pipelines that each utilized EnTAP.…”
Section: Methodsmentioning
confidence: 99%
“…The EnTAP functional annotation package was employed to remove unlikely gene models and provide provisional functional information (Hart et al 2018). Multi-exonic and mono-exonic gene models were subjected to different functional filtering pipelines that each utilized EnTAP.…”
Section: Methodsmentioning
confidence: 99%